Sistema de seguridad social en San Juan De Pasto. Línea base de la zona urbana 2008 - Ortiz Lopez, Robert Wilson; de la Cruz, Ángela Lorena; Pérez, Mildred Katherine; López, Oswaldo Aníbal; Ramírez, Iván Darío (Universidad y Salud, 2009)
A line of base of information about the Social Security System in the urban zone of the municipality of Pasto was established taking into account the research of the group “Social Conjuncture”. Some indicators were obtained and compared with the national total and relations between variables were established. These relations treat specific contents such as the insurance according to the type of regime, coverage, quality, members’ genre, and the individual appreciations of the studied population. After this, the study showed that in terms of coverage, the trends are the same as the national ones. However, in specific aspects, stand out differences arose which explained the divergence in the access conditions and provision of these services mostly reflected by the socio - economic level.